Existence of positive periodic oscillation for a competitive-cooperative model with feedback controls - Feng, Chunhua (European Journal of Applied Sciences, 2023)
In this paper, a class of nonlinear competitive-cooperative modes with feedback controls is considered. By employing the mathematical analysis method, two sufficient conditions for the existence of positive periodic solutions are obtained. Computer simulation is provided to verify the criteria. From the simulation, we see that time delays affect the oscillatory frequency